2019
DOI: 10.1007/s00011-019-01224-0
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2, but not cAMP nor β2-agonists, induce tristetraprolin (TTP) in human airway smooth muscle cells

Abstract: Tristetraprolin (TTP) is an anti-inflammatory molecule known to post-transcriptionally regulate cytokine production and is therefore an attractive drug target for chronic respiratory diseases driven by inflammation, such as asthma and chronic obstructive pulmonary disease. Our recent in vitro studies in primary human airway smooth (ASM) cells have confirmed the essential antiinflammatory role played by TTP as a critical partner in a cytokine regulatory network. However, several unanswered questions remain. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…PGE 2 also inhibited fibroblast migration, proliferation, collagen deposition, and myofibroblast differentiation in the lung ( 55 ). In vitro , PGE 2 decreased the expression of tenacin C and fibronectin by human fibroblast and ASM cells ( 56 ), reduced the proliferation of ASM cells derived from asthmatic patients ( 57 ), and upregulated the expression of the anti-inflammatory protein tristetraprolin in human ASM cells ( 58 ). Prior investigations of our group revealed that the instillation of glucagon induced a high production of PGE 2 into the lungs ( 59 ).…”
Section: Spms Derived From Cyclooxygenasesmentioning
confidence: 99%
“…PGE 2 also inhibited fibroblast migration, proliferation, collagen deposition, and myofibroblast differentiation in the lung ( 55 ). In vitro , PGE 2 decreased the expression of tenacin C and fibronectin by human fibroblast and ASM cells ( 56 ), reduced the proliferation of ASM cells derived from asthmatic patients ( 57 ), and upregulated the expression of the anti-inflammatory protein tristetraprolin in human ASM cells ( 58 ). Prior investigations of our group revealed that the instillation of glucagon induced a high production of PGE 2 into the lungs ( 59 ).…”
Section: Spms Derived From Cyclooxygenasesmentioning
confidence: 99%